1990
DOI: 10.1111/j.1348-0421.1990.tb01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Response of Murine Peritoneal Macrophages to in vitro Activation by Muramyl Dipeptide (MDP)

Abstract: Peritoneal exudate macrophages from mice, rats, and guinea pigs were assessed using six different parameters of macrophage activation to determine whether

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…25 However, Nagao et al 26 claimed that peptidoglycan and MDP failed to induced IL-1 and TNF in murine macrophage cultures, which is contrary to the positive results with guinea-pig macrophages and human monocyte cultures. Controversy still exists as to the responsiveness of murine macrophages to peptidoglycan and MDP.…”
Section: Discussioncontrasting
confidence: 49%
“…25 However, Nagao et al 26 claimed that peptidoglycan and MDP failed to induced IL-1 and TNF in murine macrophage cultures, which is contrary to the positive results with guinea-pig macrophages and human monocyte cultures. Controversy still exists as to the responsiveness of murine macrophages to peptidoglycan and MDP.…”
Section: Discussioncontrasting
confidence: 49%
“…These two studies both consider that the used compounds are recognized equally well by mouse and human NOD1. However, it must be noted that species dependency of MDP sensing has been reported [10,23], opening up the possibility that species differences may exist for agonist specificity of both NOD1 and NOD2.…”
Section: Discussionmentioning
confidence: 99%
“…Nagao et al (23,24) reported species dependency of in vitro macrophage activation by peptidoglycans and MDP; guinea pig and rat cells were responsive, but murine cells were not. In human peripheral blood mononuclear cell cultures, MDP is a powerful cytokine inducer comparable to LPS.…”
Section: Discussionmentioning
confidence: 99%